Applicant attraction and employees’ selection processes - Kaynatan, Katya Selin (2022)
This work explores the recruitment process. It analyzes how companies attract candidates and the basis for their decisions regarding who to hire. The author primarily focused on business graduates as well as ways to improve their hiring experience. Analysis was done through interviews. As for the participants of semi-structured interviews author randomly selected 15 upcoming graduates from the BBA program at Prague University of Economics and Business. During which the following points were highlighted. When searching for a job, future business graduates do not consider job fairs to be an effective channel. On the skill side, students lack Czech language skills, high-level excel knowledge, and experience. Namely, these are considered points of potential improvement in students' hiring experience. The author suggested the possible solutions in favor of graduate hiring experience.